Lessons of the 1999 Abolition of Intra-EU Duty Free Sales for Eastern European EU Candidates - Andrea Gebauer; Chang Woon Nam; Rüdiger Parsche (European Regional Science Association (ERSA), 2004)
At the end of June 1999 the intra-EU duty free shopping was abolished among the fifteen member nations. The opponents of this resolution argued that such a tax-free sales sector created jobs EU-wide and hardly reduced the value added and excise tax revenue of individual countries. In their opinion, duty free trade not only contributed to the reduction of travel fare within the EU but could also be characterised as a supplement to the normal retail trade for some products. Such `old' ideas are increasingly popular in some Eastern European EU candidates where they are preparing for the introduction of the Single Market and EU membership in the near future. This study primarily shows that the arguments mentioned above were neither significant enough nor conclusive to maintain the intra-EU duty free shopping. Furthermore, the abolition of such tax free sales was approved in the EU in order to ensure the allocation efficiency of the VAT and excise tax system within a single market. Several arguments against the intra-EU tax free shop-ping examined in the study provide some helpful policy orientations for EU membership candidates.
Keywords: 330